2009
DOI: 10.1007/s11224-009-9418-z
|View full text |Cite
|
Sign up to set email alerts
|

1D and 2D solid-state metallosupramolecular arrays of freebase 5,10,15,20-tetra(4-pyridyl)porphyrin, peripherally linked by zinc and manganese ions

Abstract: Freebase 5,10,15,20-tetra(4-pyridyl)porphyrin (TPyP) is able to assemble into crystalline rigid 1D and 2D metallosupramolecular arrrays via exocyclic coordination with tetracoordinate and hexacoordinate metal ions, respectively. In this contribution we report on two coordination polymers of l 4 -bridging freebase TPyP with zinc and manganese halide moieties. The structure of [(ZnBr 2 ) 2 TPyP] Á 6 TCE (2) (TCE = 1,1,2,2-tetrachloroethane) consists of 1D polymeric chains. The topology of [(MnCl 2 )TPyP] Á 6 TCE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 32 publications
3
17
0
Order By: Relevance
“…The AX type is composed of alternating units A and X, both four-connected, whereas in the AX 2 type A (four-connected) is linked through X (two-connected). We 4 and others 5,6 have reported 2D sheet polymers based on the regular (4,4) square grid of the AX type constructed from H 2 TPyP and transconfigured octahedral metal nodes. Examples of the AX 2 type have first been reported by Carlucci et al, containing Ag + ions as the linear metal connectors.…”
mentioning
confidence: 99%
“…The AX type is composed of alternating units A and X, both four-connected, whereas in the AX 2 type A (four-connected) is linked through X (two-connected). We 4 and others 5,6 have reported 2D sheet polymers based on the regular (4,4) square grid of the AX type constructed from H 2 TPyP and transconfigured octahedral metal nodes. Examples of the AX 2 type have first been reported by Carlucci et al, containing Ag + ions as the linear metal connectors.…”
mentioning
confidence: 99%
“…This approach has consequently been used in crystal engineering of H 2 TPyP coordination polymers 11 as well as hydrogen‐bonded assemblies 12. Herein, the chelating ligand ethylenediamine was used firstly to prevent instant formation of precipitate at the solvent interface 4, and secondly in attempting to protect potential coordination sites at the metal ion 13. The X‐ray analyses revealed, however, the formation of neutral 2D coordination arrays of the composition [Zn X 2 (μ 3 ‐ZnTPyP)·3TCE] n [ X = Cl ( 1 ), Br ( 2 )].…”
Section: Resultsmentioning
confidence: 99%
“…In a seminal work, Sharma et al reported the first heteromolecular 1D tape and 2D grid coordination polymers of the free‐base H 2 TPyP bearing Hg 2+ and Cd 2+ or Pb 2+ dihalide units as external metal linkers, respectively 3. Recently, we have shown the possibility of replacing the tetracoordinate Hg 2+ by Zn 2+ 4. In contrast to its heavier group homologue, Zn 2+ fits readily into the tetrapyrrole core of the porphyrin.…”
Section: Introductionmentioning
confidence: 99%
“…Similar coordination modes have also been reported in some documents. [18][19][20][21] So, we can infer that the structures of the assemblies should be as shown in Scheme 1. These structures were further confirmed by the TEM images and computational calculation analyses.…”
Section: Preparation Of the Assembliesmentioning
confidence: 99%